2005
DOI: 10.1002/jcb.20412
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic aspects of bladder cancer

Abstract: Transitional cell carcinoma of the urinary bladder has a diverse collection of biologic and functional characteristics. This is reflected in differing clinical courses. The diagnosis of bladder cancer is based on the information provided by cystoscopy, the gold standard in combination with urinary cytology findings. Many tumor markers have been evaluated for detecting and monitoring the disease in serum, bladder washes, and urinary specimens. However, none of these biomarkers reported to date has shown suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…chromosome aberrations, somatic mutations of other oncogenes/tumor suppressor genes, epigenetic alterations) ultimately pave the way for tumor progression and, ultimately, metastasis. [73,74] Cytogenetic and molecular genetic studies have identified large-scale structural and numerical chromosome abnormalities as predictors of bladder tumor recurrence and cancer progression. Loss of 9q is the most commonly seen abnormality in low-and high-grade tumors, suggesting that it may be a primary event in the genesis of TCCUT, but the underlying genetic mechanisms (e.g.…”
Section: High-penetrance Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…chromosome aberrations, somatic mutations of other oncogenes/tumor suppressor genes, epigenetic alterations) ultimately pave the way for tumor progression and, ultimately, metastasis. [73,74] Cytogenetic and molecular genetic studies have identified large-scale structural and numerical chromosome abnormalities as predictors of bladder tumor recurrence and cancer progression. Loss of 9q is the most commonly seen abnormality in low-and high-grade tumors, suggesting that it may be a primary event in the genesis of TCCUT, but the underlying genetic mechanisms (e.g.…”
Section: High-penetrance Genesmentioning
confidence: 99%
“…Although these genetic alterations confer only small-to-modest levels of risk, their high prevalence potentially explains a significant proportion of a given cancer's etiology. Numerous single nucleotide polymorphisms in many genes involved in genetic pathways such as carcinogen metabolism, DNA repair, and cell cycle control have been studied as candidate bladder cancer risk modifiers, but results have been inconsistent and meta-analyses have typically not been performed [2,73,78]. A complete review of these studies is beyond the scope of this manuscript; however the references cited above provide additional detail on this subject.…”
Section: Low-penetrance Genesmentioning
confidence: 99%
“…With this technology, the RNA expression levels of hundreds or even thousands of genes in a tumor can be surveyed simultaneously. The use of high throughput technologies to assess gene expression patterns in tissues, exfoliated cells in urine, or molecules in serum and in circulating cells for many malignancies, including bladder cancer, has been reported [6,7]. These studies open a door to the possibility of rapidly assessing gene expression patterns in individual tumors to determine tumor classification [8], or to predict clinical outcomes [9,10] and response to chemotherapy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary bladder neoplasms are associated with diverse biological and functional characteristics as reflected by differences in clinical course/outcomes during disease progression [8]. Such diversity in clinical course as well as outcomes is possibly due to genetic differences that make some individuals more susceptible than others.…”
mentioning
confidence: 99%